The decision making process for the exploitation of university patents through licensing to established companies and spin-off formations - Ismail, Kamariah; Abdul Majid, Izaidin; Mason, Colin; Cooper, Sarah; Wan Omar, Wan Zaidi (2008)
The commercialisation of university patents via licensing to established companies or spin-off formations are the common methods adopted by universities to exploit their patents. This paper looks very closely into who were involved and how the decision-making were made by one university to patent and through which route to exploit its portfolio of patents.